Notes on the genus Macromia Rambur, 1842 of Assam, northeast India (Anisoptera: Macromidae) - Payra, Arajush; Philip, Joel George; Islam, Nazrul; Mardi, Saurabh; Thakuria, Dipti; Koparde, Pankaj (Zootaxa, 2026)
The present paper reports Macromia sombui Vick, 1988 for the first time from India, almost 36 years after its first description from Royal Chitwan National Park of Nepal in 1988. Macromia calliope flavocolorata Fraser, 1922 and Macromia cingulata Rambur, 1842 are reported here for the first time from the northeast India based on specimens collected from the fringe area of Raimona National Park, Kachugaon Division, Bodoland Territorial Council (BTC), Assam, India. In addition, this paper incorporates Macromia cupricincta Fraser, 1924 into the Odonata list of Assam.